Hubungan Tingkat Kehadiran dengan Hasil Belajar Statistik Mahasiswa - Lalu Saparwadi (LANCAH: Jurnal Inovasi dan Tren, 2024)
In every life, humans always experience a learning process. Through learning activities, an individual will experience a change in himself. One form of each individual's readiness to learn is attendance in class. The aim of this research is to determine the relationship between attendance levels and student learning outcomes in social statistics courses. This research is associative research whose aim is to determine the relationship between two or more variables. The sample selected in this research was 24 students. The research method used in this research is the documentation method. The data analysis used in this research is descriptive quantitative data analysis and inferential quantitative data analysis with the help of SPSS 16. The results of this research show that there is a positive relationship between the level of student attendance and student learning outcomes in the Statistics course. These results show that student learning outcomes in courses are greatly influenced by the level of student attendance in statistics courses.